Macro and micronutrient intake during pregnancy: Evaluation according to maternal education and income - Taynara Suelen de Paula; Lahis Cristina Morais de Moura; Laudicéia Ferreira Fróis; João Paulo Lima de Oliveira; Letícia Vitória Cunha Silva; Lílian Gonçalves Teixeira (Revista Brasileira de Obesidade, Nutrição e Emagrecimento, 2023)
Pregnancy implies physiological and metabolic changes and changes in nutritional recommendations as well as in food habits and consumption. Considering all the factors that surround pregnancy, it is necessary to evaluate food intake during this period. The aim of this study was to investigate and identify whether sociodemographic factors such as education and income can influence the intake of macro and micronutrients by pregnant women. This is a cross-sectional study carried out with 198 pregnant women living in the city of Lavras-MG. Sociodemographic, obstetric and habitual food intake data were collected. SPSS version 20.0 was used for statistical analysis, presented by descriptive statistics and ANOVA variance analysis test. The mean age of the pregnant women was 27 ± 5.98 years. Of these, 61.1% had 8 to 11 years of schooling and 49% had an income of 1 to 2 minimum wages. It was evidenced that pregnant women with lower educational level presented a higher intake of carbohydrates, potassium and vitamin B3. Pregnant women with higher income had higher intake of vitamin C, cholesterol and percentage of lipids, as well as lower percentage of carbohydrates (considering daily energy). On the other hand, pregnant women with lower income had a lower intake of monounsaturated fat and vitamin B12. We conclude that maternal education and income influence the intake of macro and micronutrients. It is extremely important to develop public policies aimed at efficient nutritional intervention during prenatal care, in order to promote maternal and child health.